On quasilinear elliptic equations in ℝN. (1996) - Alves, C. O.; Concalves, J. V.; Maia, L. A.
Abstract : In this note we give a result for the operatorp -Laplacian complementing a theorem by Brézis and Kamin concerning a necessary and sufficient condition for the equation− Δ u = h ( x ) u q inℝ N, where0 < q < 1, to have a bounded positive solution. While Brézis and Kamin use the method of sub and super solutions, we employ variational arguments for the existence of solutions.